The changing human-nature relationship (HNR) in the context of GEC - Bernhard Glaeser (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
The overall objective of this introductory essay is to convey a broad view of social and cultural aspects of global environmental change (GEC). It represents a Western, social science perspective, and reflects on today.s discourses as influenced or characterized by the turn from the second to the third millennium. The article opens with some remarks concerning the relationship between natural and social change (part 1). Part 2 raises the question, .to what extent is nature peripheral to humans?. Part 3 focuses on present interpretations of how a millennial shift is experienced: .Do the social and interdisciplinary sciences take notice of the human-nature relationship (HNR) in the context of GEC?. An important new topic in world politics and in the social sciences will be the social dimension of sustainability, including social exclusion and development, as argued in part 4. In part 5, the final section, conclusions are drawn about historical, theoretical, ethico-behavioral, and political aspects of the HNR within the context of GEC. It is concluded that the international scientific community can and should play a vital role in finding solutions to sustain the environmental conditions for the sake of global livelihood, including social justice. – – Das Ziel des Einführungs-Essay ist es, eine breite Sicht der sozialen und kulturellen Aspekte globaler Umweltveränderung (GEC) zu vermitteln. Er steht für eine westlichsozialwissenschaftliche Perspektive und ist aktuellen Diskursen an der Schwelle zum 3. Jahrtausend u. Z. verpflichtet. Der Beitrag wird eröffnet mit einigen Bemerkungen zum Verhältnis zwischen natürlichem und sozialen Wandel (Teil 1). Teil 2 stellt die Frage, inwieweit Natur für Menschen peripher ist. Dies wird an Beispielen für die sozialwissenschaftliche und interdisziplinäre Veröffentlichungspolitik interpretiert (Teil 3). In Teil 4 wird argumentiert, dass eine wichtige neue Thematik für die Weltpolitik ebenso wie für Sozialwissenschaften die soziale Dimension der Nachhaltigkeit sein wird, soziale Exklusion und Entwicklungsproblematik eingeschlossen. Der abschließende Teil 5 zieht Schlussfolgerungen für historische, theoretische, ethische und politische Aspekte der Mensch-Natur- Beziehung im Rahmen globaler Umweltveränderungen. In der Zuspitzung heißt dies, dass die internationale epistemische Gemeinschaft eine entscheidende Rolle bei der Findung nachhaltiger Umweltbedingungen für eine sozial gerechte globale Gesellschaft spielen kann und soll.
Keywords: 300